Erratum - Goin, Francisco Javier; Case, Judd A.; Woodburne, Michael O.; Vizcaíno, Sergio Fabián; Reguero, Marcelo Alfredo
In the December 1999 issue of the Journal of Mammalian Evolution (Vol. 6, number4: 335?365), technical difficulties resulted in some of the figures published by Francisco J. Goin et al., in their paper ?New Discoveries of Opossumlike? marsupials from Antarctica (Seymour Island, Medial Eocene),? being of poor quality. The following new images are presented here. In that they are based on new SEM photos taken of the original specimens, not all views are exactly comparable with the original figures. New captions are provided for the figures given here. Fil: Goin, Francisco Javier. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Case, Judd A. St. Mary's College of California; Estados Unidos Fil: Woodburne, Michael O. University of California; Estados Unidos Fil: Vizcaíno, Sergio Fabián. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina